ANALISI FAKTOR-FAKTOR YANG PENGARUHI PAJAK DAERAH KABUPATEN EKS-KARESIDENAN SURAKARTA - Shodhik Ade Gunawan; Fadjar Harimurti; Sunarti Sunarti (Universitas Slamet Riyadi, 2020)
This study aims to examine the influence and analysis of PDRB, population, inflation and number of industries on the tax revenue of the ex-residency district of Surakarta. This study uses a survey method as an instrument. The population of this study is LKPD and BPS data of the Surakarta Ex-Residency District. Based on the purposive sampling method, the number of samples obtained was 35 data. This type of research used in this research is quantitative research with the aim to uncover the truth contained in this research problem with multiple regression testing and class assumption testing and data analysis to determine the quality used with the help of SPSS 25 software. The results of this study indicate that partially PDRB variable, Total Population, Inflation and Number of industries affect the Local Tax Revenue. This research is expected to be able to provide useful input for regional governments to synergize with each other to further increase Regional Tax Revenues.